A social comparison theory approach to mothers' and daughters' clothing co-consumption behaviors: A cross-cultural study in France and Japan - Gentina, Elodie; Huarng, Kun-Huang; Sakashita, Mototaka (Journal of business research, 2018)
Much remains unknown about the clothing co-consumption practices of mothers and their teenage daughters, especially from a cross-cultural perspective. This study uses social comparison theory to examine how mothers engage in clothing co-consumption practices with their adolescent daughters and the effects on their likelihood of changing brands, stores, or styles. It includes 732 French and Japanese mothers who have adolescent daughters between the ages of 15 and 18years. The structural equation modeling and qualitative analysis with structural associations reveal that Japanese mothers with high self-esteem enter into strong social comparisons, which lead to co-consumption practices (common shopping, joint purchases, clothing exchanges), whereas regardless of their levels of self-esteem, French mothers engage in social comparison processes that lead them to change their clothing styles, brands, and stores.